Konsep Jual Beli dalam Islam dan Implementasinya pada Marketplace - Khatimah, Husnul; Nuradi, Nuradi; Alim, Akhmad (ITB AAS INDONESIA Surakarta, 2024)
Islam is very concerned about all aspects of the lives of its adherents including the problem of buying and selling, especially the development of technology today makes transactions between sellers and buyers do not have to meet directly and products do not have to be delivered at that time. The purpose of the research is to find out how the concept of buying and selling in Islam and its implementation in the marketplace. This research uses a library research method with a descriptive qualitative approach, which describes and summarizes various variables and their situations and conditions. The results showed that the concept of buying and selling in Islam is based on the rules in fiqh muamalah that the original law of a muamalah activity is al-ibahah (permissible) as long as there is no evidence that prohibits it. The implementation of the concept of buying and selling in Islam in the marketplace based on the description of the marketplace transaction scheme in general, there are no transaction problems in it for both sellers and consumers, because it only acts as an online market that brings together a group of sellers and buyers.